High Occurrence of Emerged Lophomonas Infection among Patients Suspected of Having Pulmonary Tuberculosis: In-House PCR-Based Evidence - Hamed Kalani; Ayeneh Pangh; Maryam Nakhaei; Hajar Ziaei Hezarjaribi; Mahdi Fakhar; Ali Sharifpour; Elham Sadat Banimostafavi; Rabeeh Tabaripour (Interdisciplinary Perspectives on Infectious Diseases)
Objectives. Lophomonas infection is a respiratory disease in humans that is associated with symptoms of cough, sputum, dyspnea, and sometimes hemoptysis, which shows the importance of differentiating this disease from tuberculosis and asthma. Methods. This study was performed on 216 participants suspected of having tuberculosis who had symptoms of fever, chronic cough, or sputum and were referred to tuberculosis laboratories in three cities in Golestan Province, northeastern Iran, during 2019-2020. A sputum sample was taken from the suspected patients. DNA was extracted from the frozen samples, and an in-house polymerase chain reaction was performed to detect the Lophomonas DNA. Results. Out of 216 subjects, 47 (21.75%) were infected with Lophomonas spp. Moreover, 9 patients (4.2%) were infected with tuberculosis. Also, 2 patients had a comorbidity of tuberculosis and Lophomonas infection P=0.63. There was no significant difference in the comparison of symptoms and the rate of Lophomonas infection P=0.84, but in the comparison of the set of symptoms of cough, sputum, and fever with those of cough and sputum, cough with fever, sputum with fever, and the rate of Lophomonas infection, there was a significant difference P=0.012. Conclusions. Lophomonas infection was relatively high in patients suspected of having tuberculosis and due to the similar clinical symptoms of Lophomonas infection and tuberculosis; it is recommended that the sputum samples of subjects suspected of having tuberculosis be examined for this parasite in order to make a correct diagnosis and the patients receive timely treatment and the appropriate medication.